2019
DOI: 10.1016/j.jogoh.2019.05.009
|View full text |Cite
|
Sign up to set email alerts
|

Impact of salpingectomy for ectopic pregnancy on the ovarian response during IVF stimulation

Abstract: Introduction: Ovarian reserve is a major prognosic factor for Medical Assisted Procreation. Tubal surgery, realised close to mesosalpinx and ovarian vascularization, could impare ovarian function. However, salpingectomy is currently used to treat ectopic pregnancies or hydrosalpinx before IVF attempt. Disponible studies on this subject are unclear. The aim of this study is to evaluate the impact of salpingectomy for ectopic pregnancy on the ovarian response during IVF attempt. Material and methods: It was a si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…In Mitwally et al (12) , Frates et al (13) , and Gay et al (14) the average platelet count for MTX was 251.5 on the first day of treatment and reached 162 × 103 on day seven; for letrozole, it was 214.9 on the first day of treatment and reached 213.9 × 103 on day seven. On the day of therapy, for MTX, the average AST level was 19.8 and it rose to 44.1 (U/L).…”
Section: Discussionmentioning
confidence: 94%
“…In Mitwally et al (12) , Frates et al (13) , and Gay et al (14) the average platelet count for MTX was 251.5 on the first day of treatment and reached 162 × 103 on day seven; for letrozole, it was 214.9 on the first day of treatment and reached 213.9 × 103 on day seven. On the day of therapy, for MTX, the average AST level was 19.8 and it rose to 44.1 (U/L).…”
Section: Discussionmentioning
confidence: 94%
“…Moreover, both PID and salpingectomy, especially bilateral, lead to infertility, thus increasing the demand for in vitro fertilization (IVF) in Kazakhstan [ 38 , 39 ]. Although some studies have found that unilateral salpingectomy for ectopic pregnancy by itself does not impair the ovarian reserve and response during IVF stimulation [ 40 , 41 ], contradictory results were reported for bilateral surgery [ 27 ]. Moreover, psychological stress related to the loss of tubes and subsequent sterility might contribute to the psychological distress existing in patients undergoing IVF procedures [ 38 , 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…This finding could be explained by the effect of tubal surgery for EP on ovarian reserve and ovarian response. Because ovarian vascularization is close to the fallopian tube and mesosalpinx, tubal surgery may impair ovarian vascularization and function [ 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%